RELASI AL-QUR'AN, AKAL, DAN FILSAFAT: IMPLIKASI BAGI PENDIDIKAN ISLAM DI ERA GLOBAL - Maryam; Saiful Anwar (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study examines the relationship between the Qur'an, intellect, and Islamic educational philosophy in the context of global educational challenges. Departing from previous research, this study offers a new perspective on the integration of revelation and reason as a solution to strengthen the relevance of Islamic education in the modern era. Using a literature-based qualitative research method, this study collects and analyzes various relevant literature to understand the relationship between Qur'anic values, reason, and philosophy in the Islamic education system. The results of the study show that the Qur'an provides a moral and spiritual foundation for Islamic education, while the intellect serves as a tool to understand and apply these values in learning. The philosophy of Islamic education integrates these two elements, so that it is able to form human beings with noble character, knowledge, and contribute positively to society. In the modern era, Islamic educational philosophy remains relevant in facing the challenges of globalization, moral crises, and technological developments. By emphasizing monotheism, morality, and knowledge as the main pillars, this philosophy is able to produce a generation that is not only intellectually intelligent, but also has strong moral and spiritual integrity. This research contributes to the development of Islamic educational theory and practice by providing practical guidance for the implementation of Qur'anic values and philosophies in the modern education system. In conclusion, the integration between revelation and reason is a holistic approach that not only answers the needs of today's education but also maintains the Islamic identity of the ummah in the midst of changing times.